Promoting racial literacy in early childhood: Storybooks and conversations with young black children. (17th January 2022) - Curenton, Stephanie M.; Harris, Keshia; Rochester, Shana E.; Sims, Jacqueline; Ibekwe‐Okafor, Nneka
Abstract: Racial literacy as defined by Stevenson (2014) is an important cultural resistance strategy (e.g., positive coping strategy) for Black children and youth because it gives them the skills needed to survive in a racist society. Stevenson's work, along with the work of several of his colleagues, focuses on adolescents and those in middle childhood, yet it has inspired us to postulate how racial literacy might be fostered in young children (ages 3–8). In this article, we propose a theoretical model for how racial literary can be fostered within shared‐reading contexts using racially affirming storybooks coupled with conversations grounded in the principles of ethnic‐racial socialization. We also propose that these conversations result in both a direct influence on racial literacy and an indirect influence via positive ethnic‐racial identity and emotion regulation and understanding.